Subcutaneous adipose tissue metabolism studied by local catheterization. - Frayn, K; Coppack, S; Humphreys, S (1993)
Adipose tissue is a metabolically active tissue which plays a key role in regulating the concentrations of circulating lipid fuels. In recent years, two new techniques have become available for the study of human adipose tissue metabolism in vivo: microdialysis, and catheterization of the venous drainage from the subcutaneous abdominal adipose tissue. Blood obtained by the latter method shows all the characteristics expected of adipose tissue drainage. The characteristics of this tissue are quite distinct from those of the superficial (mainly skin) or the deep (mainly muscle) tissues of the forearm. The depot studied appears to be typical of adipose tissue as a whole in terms of non-esterified fatty acid release. In comparison with the microdialysis technique, the arterio-venous difference technique allows easier quantification of substrate uptake and release, and allows the study of hydrophobic molecules (e.g. fatty acids, triacylglycerol). On the other hand, it does not allow the study of more than one depot, nor the local introduction of effectors of metabolism (e.g. adrenergic agents). The two techniques are clearly complementary.